Avaliação da qualidade da comunicação no atendimento terciário em oftalmologia - Bernardo, Marlene [UNIFESP] (2017)
Objective: The objective of this study was to evaluate the quality of communication during patient care in a tertiary eye care service. For in the health area, communication has a direct impact on health status and patient care since it permeates the correct understanding of diagnosis, adherence to treatment, as well as its risks and benefits. Method: We included users of a federal public university hospital; being that the users less than 18 years and with verbal or cognitive deficit were represented by their respective parents / companions. A questionnaire was developed to evaluate the quality of communication in the customer service with closed questions of ordinal classification, and the interviews were conducted by a single interviewer. The questions were grouped in domains according to the type of care received by the user: communication of the reception / scheduling team and communication of the medical team and ophthalmic technologists. Two other domains were evaluated: verbal and non-verbal communication. Each question received a score of zero, 25, 50, 75 or 100, according to the classification assigned by the participant, representing the frequency with which he experienced specific situations associated with attendance. The higher the score, the greater the satisfaction of the participant in the area investigated, that is, the satisfaction with the service performed. For each domain and subdomain, the arithmetic mean of the score obtained in the related questions was calculated. In the end, the overall quality score of the communication in the care was calculated. Verbal communication, non-verbal communication scores and overall quality of care communication score were analyzed according to age, sex, schooling and family income. The statistical models used were Student's t-test, paired t-test, one-way ANOVA and Pearson's correlation. When there was no normal distribution of the variables, the nonparametric tests of Mann Whitney, Wilcoxon, Kruskal-Wallis ANOVA (followed by the Dunnet or Tukey multiple comparisons test) and Spearman's correlation were used. The internal consistency of the responses was measured by Cronbach's alpha coefficient. The level of statistical significance was considered as p≤0.05 with two-tailed rejection region. Results: Of the 257 interviewed users, 126 (49.0%) were male and 131 (51.0%) were female. The participants' ages ranged from 18 to 84 years (mean = 44 ± 17 years, median = 43 years). Cronbach's alpha coefficient showed good internal consistency of responses for all domains: communication from the reception / scheduling team, communication from the medical team / ophthalmic technologists, verbal communication, non-verbal communication and global communication quality score, being 0.83 , 0.78, 0.65, 0.80 and 0.62, respectively. The overall quality score of the communication was 64.2, and the overall quality score of the communication of care was 64.2. The calculated score for the attendance of the reception / scheduling team (61.7) was on average statistically lower when compared to the value calculated for the medical team / ophthalmic technologists (68.6, p <0.001). Regarding verbal communication, the calculated score for the reception / scheduling team (62.0) was statistically lower when compared to the value obtained by the medical team / ophthalmic technologists (75.8, p <0.001). However, in relation to non-verbal communication, we observed the inverse (p <0.001). There was no association between age and mean scores calculated for verbal, nonverbal communication and overall quality of communication in care. The mean scores calculated for male and female participants were statistically comparable. Participants with higher or higher scores attributed, on average, significantly lower scores on verbal communication and overall quality compared to those with medium level (p = 0.0180 and p = 0.0369, respectively). In the participants with family income of 4 to 6 minimum wages, the score attributed to verbal communication was statistically lower (p = 0.0190). Conclusions: The overall quality of communication in care (64.2) and the score assigned by the users to the communication in the service (8.2) indicate that the quality of communication in the tertiary health care service studied was well evaluated . The communication quality assessment questionnaire was constructed and validated, allowing the measurement of this quality management indicator. The issues studied may serve as a basis for the elaboration of a user assistance manual and for the establishment of adequate internal and external communication that favors the development of an organized.